The Impact of Shopee Quality Service for The Customers Satisfaction of Making Purchases in Marimbuns Village Pematang Siantar Year 2022/2023 - Trinovlin Santika Manik; Binsar Tison Gultom; Sotarduga Sihombing (MultiTech Publisher, 2023)
This type of research is quantitative. This research was carried out to find out how the quality of Shopee service affects customer satisfaction carried out in the Tong Marimbun Pematang Siantar sub-district. The subjects of this research were the people of Tong Marimbun sub-district, taking 80 people. So the total number of people who use the Shopee application was taken, a total sample of 80 respondents was used. Data collection was carried out using library research methods, documentation, questionnaires. The results of the questionnaire have been tested for validity and reliability, in the form of normality assumptions. Data analysis techniques use normality test techniques, simple regression heteroscedicity tests , f tests and t tests. By using the Statistical Product and Service Solution (SPSS) program. The research results showed that the proposed hypothesis was accepted because it showed positive and significant hypothesis test results. This means that Shopee's online service quality has a positive and significant effect on consumer satisfaction in Tong Marimbun Pematan Siantar sub-district.